Kesiapan Calon Guru di Era Digital: Analisis Faktor Penentu dalam Meningkatkan Profesionalisme Pendidik Masa Depan - Fujianti, Indah (AL MURABBI, 2025)
Teachers are the main actors in the success of the education system. Its vital role in achieving national education goals requires the existence of professional competencies that are constantly updated, especially in the digital era. One of the absolute requirements for today's teachers is the ability to communicate effectively with students through the use of information technology. Therefore, strengthening the readiness of prospective teachers is crucial in producing educators who are professional and adaptive to the times. This study uses a descriptive qualitative approach with a case study method. Data was collected through in-depth interviews, observations, and documentation of students of education study programs who were undergoing teaching practices. The analysis was carried out by data reduction techniques, data presentation, and conclusion drawn. The results of the study show that the readiness of prospective teachers is influenced by three main factors: (1) mastery of educational technology, (2) pedagogical communication skills, and (3) field practical experience. Prospective teachers who receive adequate digital training and hands-on interaction experience with students show higher levels of readiness than others. These findings indicate that educational institutions need to design curricula based on the needs of the times, which not only emphasize theoretical aspects, but also digital practices and soft skills. Systematically increasing the readiness of prospective teachers will support the creation of a professional, effective, and globally competitive education ecosystem in the digital era.